Teaching physicians the GPGP method promotes deprescribing in both inpatient and outpatient settings. (December 2019) - Bilek, Aaron Jason; Levy, Yuval; Kab, Haneen; Andreev, Pavel; Garfinkel, Doron
Background: In complex older patients, inappropriate medication use and polypharmacy (IMUP) are commonplace and increasing exponentially. Reducing IMUP is a challenge in multiple clinical contexts, including acute admission and family practice, due to several key barriers. In the global effort against this epidemic, educational programs geared toward changing physicians' prescribing patterns represent an important means of promoting deprescribing. Methods: This is a nonrandomized, controlled interventional study investigating polypharmacy outcomes and prescribing patterns in patients whose physicians were trained in the Good Palliative-Geriatric Practice (GPGP) method, an algorithm for the reduction of polypharmacy, with patients whose physicians were not. Training involved a one-time, full-day workshop led by a senior geriatrician. Two separate settings were examined. In the inpatient setting, one internal medicine ward was trained and compared with another ward which was not trained. In the family practice setting, 28 physicians were trained and compared with practices of 15 physicians not trained. Patients were above the age of 70, representative of the general geriatric population, and not terminally ill. Results: In the inpatient arm, the intervention group ( n = 100) experienced a decrease in medications prescribed from admission to discharge of 18.5%, compared with a decrease of 1.9% in the control group ( n = 100, difference between groups p < 0.0001). In the outpatient arm, the intervention group ( n = 100) experienced a decrease in medication number of 6.1% compared with 0.07% in the control group ( n = 100, difference between groups p = 0.001) over a 6-month period. Preferential decreases in specific drug classes were observed in both groups, including benzodiazepines, psychotropics, and antihypertensives. Conclusions: A one-time educational intervention based on GPGP can change prescribing patterns in both outpatient and inpatient settings leading to a moderate reduction in polypharmacy. Future work should focus on longitudinal interventions, and longer-term clinical outcomes such as morbidity, mortality, and quality of life.